2021
DOI: 10.11648/j.ijfsb.20210602.16
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional, Functional and Sensory Properties of Gari Enhanced with Fermented Maize Residues Flour

Abstract: The by-product (residue) from fermented yellow maize starch production was dried and milled into flour and designated as fermented yellow maize residues, the residue was added to Gari at 0-30% levels of substitution to produce Gariresidue blends. The blends and control were evaluated for its functional and pasting properties, proximate composition, mineral content and starch digestibility. The Gari-residue blends were reconstituted with hot water into a stiff dough ("Eba") and its sensory and proximate composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 10 publications
(13 reference statements)
1
1
0
Order By: Relevance
“…The magnesium contents decreased as the cowpea hull increased in the EG that had their hulls fermented with the cassava mash and decreased as cowpea hull increased in the unfermented counterpart. The report of this study is significantly superior to the range 2.50 to 3.20 mg/100g reported by Owuno et al (2021) for gari fermented with maize residue. Magnesium is important In the metabolism of carbohydrates, regulates vital energy processes, blood sugar levels by improving insulin production and sensitivity thereby reducing Type-2 diabetes by 15%, support healthy immune system, helps in protein synthesis, heart rhythm steady, maintaining healthy cells, promote strong bones and normal blood pressure (Enyiukwu, 2018).…”
Section: Proximate Composition Of Cowpea Hull-enriched Garicontrasting
confidence: 81%
See 2 more Smart Citations
“…The magnesium contents decreased as the cowpea hull increased in the EG that had their hulls fermented with the cassava mash and decreased as cowpea hull increased in the unfermented counterpart. The report of this study is significantly superior to the range 2.50 to 3.20 mg/100g reported by Owuno et al (2021) for gari fermented with maize residue. Magnesium is important In the metabolism of carbohydrates, regulates vital energy processes, blood sugar levels by improving insulin production and sensitivity thereby reducing Type-2 diabetes by 15%, support healthy immune system, helps in protein synthesis, heart rhythm steady, maintaining healthy cells, promote strong bones and normal blood pressure (Enyiukwu, 2018).…”
Section: Proximate Composition Of Cowpea Hull-enriched Garicontrasting
confidence: 81%
“…The phosphorus contents ranged from 4.02 mg/100g for G 97 CF 3 (Cowpea hull added before fermentation at ratio 3%: 97% gari) to 5.04 mg/100g for G 97 CNF 3 (Cowpea hull added after fermentation at ratio 3%: 97% gari). The result obtained in this study is slightly higher than (4.04 to 4.67 mg/100g) recorded by Owuno et al, (2021) for gari fermented with maize residue. But, lower than 49.62 to 69.54 mg/100g and 16.20 to 18.62 mg/100g for soy-gari and Soy-melon enriched gari respectively (Ogunlakin et al, 2015;Oluwamukomi & Adeyemi, 2015).…”
Section: Proximate Composition Of Cowpea Hull-enriched Garicontrasting
confidence: 77%
See 1 more Smart Citation
“…The high SC obtained from the unfermented cowpea hulls samples might be due to large starch granules as reported by Olaleye et al (2013), who opined that starch with large granules exhibits higher swelling power than starch with small granules. The value obtained is higher than 3.32–4.01 g/g recorded by Adejuyitan et al (2018) for gari produced from different varieties of cassava but almost similar to 5.78–8.06 g/g recorded by Friday et al (2021) for gari fermented with yellow maize residue blends. The increase in swelling capacity is a function of an increase in solubility because swelling power depends on the ability of certain components of the food sample, most especially amylase, to solubilise in water (Moorthy et al, 2007).…”
Section: Resultssupporting
confidence: 62%
“…This study also show an increase in protein content of the unsieved samples as values were higher when compared with the control for all the grains. Owuno et al [31] reported increase in protein content of Garimaize residue blend.…”
Section: Discussionmentioning
confidence: 97%